Novel pleural-bladder pump in malignant pleural effusions: from animal model to man. Issue 5 (12th March 2020) - Astoul, Philippe; Laroumagne, Sophie; Capel, Jeroen; Maskell, Nicholas A
Abstract : Malignant pleural effusion is common and causes disabling symptoms such as breathlessness. Treatments are palliative and centred around improving symptoms and quality of life but an optimal management strategy is yet to be universally agreed. A novel pump system, allowing fluid to be moved from the pleural space to the urinary bladder, may have a role for the management of recurrent malignant pleural effusion. We hereby describe the first animal study using this device and the results of the first application in patients.